A double signal amplification platform for ultrasensitive and simultaneous detection of ascorbic acid, dopamine, uric acid and acetaminophen based on a nanocomposite of ferrocene thiolate stabilized Fe3O4@Au nanoparticles with graphene sheet - Liu, Meiling; Chen, Qiong; Lai, Cailang; Zhang, Youyu; Deng, Jianhui; Li, Haitao; Yao, Shouzhuo (Biosensors & bioelectronics, 2013)
A double signal amplification platform for ultrasensitive and simultaneous detection of ascorbic acid (AA), dopamine (DA), uric acid (UA) and acetaminophen (AC) was fabricated by a nanocomposite of ferrocene thiolate stabilized Fe3O4@Au nanoparticles with graphene sheet. The platform was constructed by coating a newly synthesized phenylethynyl ferrocene thiolate (Fc-SAc) modified Fe3O4@Au NPs coupling with graphene sheet/chitosan (GS-chitosan) on a glassy carbon electrode (GCE) surface. The Fe3O4@Au–S–Fc/GS-chitosan modified GCE exhibits a synergistic catalytic and amplification effect toward AA, DA, UA and AC oxidation. The oxidation peak currents of the four compounds on the electrode were linearly dependent on AA, DA, UA and AC concentrations in the ranges of 4–400μM, 0.5–50μM, 1–300μM and 0.3–250μM in the individual detection of each component, respectively. By simultaneously changing the concentrations of AA, DA, UA and AC, their electrochemical oxidation peaks appeared at −0.03, 0.15, 0.24 and 0.35V, and good linear current responses were obtained in the concentration ranges of 6–350, 0.5–50, 1–90 and 0.4–32μM with the detection limits of 1, 0.1, 0.2 and 0.05μM (S/N=3), respectively. •A new ferrocene benzyne derivative modified magnetic composite was firstly synthesized.•A double signal amplification platform was fabricated by a ferrocene nanocomposite.•Fe3O4@Au–S–Fc/GS-chitosan/GCE exhibits amplification effect to AA, DA, UA and AC.•Simultaneous and ultrasensitive detection of AA, DA, UA and AC were realized.